PENGARUH KUALITAS PEGAWAI TERHADAP PRESTASI KERJA PEGAWAI KANTOR KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KERTANEGARA - ., Muksoni (PREDIKSI, 2012)
Data were collected through questionnaires to 40 respondents Tenggarong Seberang Employees District Office. The collected data were analyzed by simple linear regression using SPSS for windows.The results of the data analysis showed that the quality of employees have a positive and significant impact on Employee Job Performance Across Tenggarong District Office, having known R count 0.604> 0.312 R table, and value significance of 0000 is less than 0.05.Rated R Square of 36.5 percent, meaning that employees can affect the quality of Employees Occupational Performance Across the District Office Tenggarong Kutai Kartanegara of 36.5 percent, while the remaining 63.5 percent were not influenced by other variables examined in this study.